Psychological Bias of Chinese Investors Due to Overconfidence- Take “Tik-Tok” for Example - Meng, Zini (BCP Business & Management, 2022)
In many cases we’ve found that when a company CEO is overconfident, it has a major impact on decision making, and often puts a company’s future at risk. Through a modern case study in such overconfidence, I examine the causes of psychological overconfidence in its various forms The case of Tik-Tok allows us to look at the moderating impact of overconfidence bias and decision-making by investors. We learn that prudence and indeed fear of making mistakes are reasons for successful investment.